IOT Hidroponik Indoor Menggunakan Growing Light Dan Sirkulasi Udara Dalam Air - Eka Budhy Prasetya; khairur rozikin (Tekinfo: Jurnal Bidang Teknik Industri dan Teknik Informatika, 2021)
Plant cultivation using hydroponic systems is a trend of urban agriculture. The most important thing in hydroponic systems is water and plant irradiation. Radiation with the sun can hardly be done in indoor hydroponic systems. Therefore, to make the radiation can be done using lights to grow the lights. To turn the lights on and off for hydroponic irradiation must be adapted to the needs of light, irrigation, and nutrition. Then it needs to be turned on and the lights and nutrition irrigation is still enough. Need grow optimally the water in circulation so that the plants. Arduino Uno as a controller sensor consists of ultrasonic sensors, RTC modules, relays, NodeMCU, I2C LCDs, Wavecom Modems, Raspberry pi3, dimmers, dc motors, solenoid valves, and growing lights. RTC functions for a dc motor by using a relay. Ultrasonic sensors are used to measure the height which will then be forwarded via SMS if water must be added. Send SMS using the SMS Gateway connected by Raspberry that is connected to the Wavecom modem and NodeMCU. This system can be used in hydroponic cultivation for consumption or personal decoration. Keywords: Hydroponic System Wick,Growing Lights,SMS gateway Arduino Uno, Raspberry